ANALYZING THE IMPACT OF COMPANY FINANCIAL PERFORMANCE ON STOCK RETURNS OF THE FOOD & BEVERAGE COMPANIES LISTED IN INDONESIAN STOCK EXCHANGE (IDX) FROM PERIOD 2018 â 2022 - Ramadhan, Mustafa
This research studies the relationship between financial performance using proxies for the solvency ratio (Debt to Equity Ratio, DER), profitability ratio (Return on Equity Ratio, ROE), and liquidity ratio (Current Ratio, CR) with stock returns. Using a population of food & beverage sub-sector companies listed in the Indonesia Stock Exchange, this research obtained 10 research samples studied in the 2018-2022 period. The result of this research is that the F-test test found that DER, ROE, and CR simultaneously are able to explain variations and contribute to stock returns. The ttest showed that ROE has a positive and significant influence on stock returns. Meanwhile, DER and CR were found to have no significant effect on stock returns.